2011
DOI: 10.1016/j.jfineco.2010.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Investor sentiment and the mean–variance relation☆

Abstract: This study shows the influence of investor sentiment on the market's mean-variance tradeoff. We find that the stock market's expected excess return is positively related to the market's conditional variance in lowsentiment periods but unrelated to variance in high-sentiment periods. These findings are consistent with sentiment traders who, during the high-sentiment periods, undermine an otherwise positive mean-variance tradeoff. We also find that the negative correlation between returns and contemporaneous vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
247
5
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(286 citation statements)
references
References 87 publications
23
247
5
3
Order By: Relevance
“…The premise that investor sentiment has a significant impact on determining stock values has been used in a number of studies that analyze the relationship between returns and an investor sentiment index, producing evidence that sentiment does have an influence on stock prices (Baker & Wurgler, 2006, 2007Baker, Wurgler, & Yuan, 2012;Barberis, Shleifer, & Vishny, 1998;Brown & Cliff, 2004;Delong, Shleifer, Summers, & Waldmann, 1990;Shiller, 2000;Stambaugh et al, 2012;Yu, 2013;Yu & Yuan, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The premise that investor sentiment has a significant impact on determining stock values has been used in a number of studies that analyze the relationship between returns and an investor sentiment index, producing evidence that sentiment does have an influence on stock prices (Baker & Wurgler, 2006, 2007Baker, Wurgler, & Yuan, 2012;Barberis, Shleifer, & Vishny, 1998;Brown & Cliff, 2004;Delong, Shleifer, Summers, & Waldmann, 1990;Shiller, 2000;Stambaugh et al, 2012;Yu, 2013;Yu & Yuan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a number of studies have found empirical evidence that investor sentiment can possibly contain a vast market component capable of driving the prices of several assets at once towards a specific direction (Baker & Wurgler, 2006, 2007Baker et al, 2012;Brown & Cliff, 2004;Stambaugh et al, 2012;Yu & Yuan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is broad agreement that, even after controlling for "rational" influences such as meanvariance (Yu and Yuan, 2011) and Fama-French factors 3 (Xu and Green, 2013), indicators of sentiment do contribute significantly to explaining the time series and cross-sectional behaviour of stock returns in a variety of settings. The preponderance of the evidence from a variety of datasets and measures of sentiment is that unusually high levels of sentiment tend to be associated with increased trading (Brown, 1999), greater volatility (Lee, Jiang and Indro, 2002), and lower returns (Brown and Cliff, 2004;Schmeling, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Brandt and Kang (2004) model both the expected returns and conditional variance as latent variables in a multivariate framework and find a negative trade-off. Alternatively, Yu and Yuan (2011) use data on investor sentiment to study the risk-return trade-off. They find that expected returns and conditional variance are positively related in low-sentiment periods, but unrelated during high-sentiment periods.…”
Section: Introductionmentioning
confidence: 99%